A novel c-type lysozyme from Litopenaeus vannamei exhibits potent antimicrobial activity. Issue 131 (December 2022) - Hu, Feng; Wang, Yan; Hu, Jingjie; Bao, Zhenmin; Wang, Mengqiang
Abstract: Lysozyme is relevant to the innate immune system as a vital protein for crustaceans. In the present study, we cloned and characterized a novel c-type lysozyme gene ( Lv LYZ) from the Pacific white shrimp ( Litopenaeus vannamei ). The obtained full-length cDNA of Lv LYZ was 990 bp and contained an open reading frame of 693 bp. Its deduced amino acid sequence consisted of 230 amino acids (aa) with a 17 aa signal peptide at the N-terminal and 130 aa functional domains. The multiple sequence alignment (MSA) indicated that the typical active sites in Lv LYZ were similarly conserved as c-type lysozymes from other species. The transcription of Lv LYZ appeared in all detected tissues and had relatively higher expression levels in hemocytes, hepatopancreas, gill and intestine. The mRNA expression profiles of Lv LYZ were up-regulated in hemocyte and hepatopancreas post the stimulation of Vibrio parahaemolyticus or white spot syndrome virus (WSSV), respectively. The recombinant protein of Lv LYZ (r Lv LYZ) exhibited antibacterial activities against various microbes, including Escherichia coli, Vibrio splendidus, Micrococcaus luteus, Vibrio parahaemolyticus and Staphylococcus aureus . These results indicated that Lv LYZ could cope with bacteria in L. vannamei and may play a significant role in immune response against invading pathogens. Highlights: A novel c-type lysozyme gene from Litopenaeus vannamei was cloned. The c-type lysozyme shared a significant homology with other shrimp lysozyme proteins. The c-type lysozyme was differentially expressed in all examined tissues. The c-type lysozyme gene was involved in immune response and its recombinant protein exhibited potent antimicrobial activity.